Pendekatan pembelajaran melalui bermain untuk meningkatkan kemahiran murid membatangkan suku kata terbuka kv+kv menggunakan teknologi realiti maya - Jumaat, Nurul Farhana (2018)
Reading skills range from recognizing, recognizing and speaking letters, speaking syllables, speaking syllables and reading words and sentences. However, there are still some students who cannot master the skills of developing simple two syllables consisting of kv + kv patterns especially among linseed students. Therefore, this study used a play-by-play approach to improve pupils' ability to express kv + kv open syllables because play is a natural way of children. In the meantime, researchers have also created a technology innovation in the form of virtual reality technology or Virtual Reality (VR) to help students with this problem. A total of 10 students at one of the Tamil national schools participated in the study. As a result of the observations and interviews of all 10 students, they expressed their interest in learning by playing with virtual reality technology. Pre and post exams. The interview results showed a significant improvement after use. Furthermore, this demonstrates that the use of virtual reality technology has contributed to the improvement of kv + kv syllabus skills among linseed students. Discussions and suggestions for further research are included in this study